A Data-Driven Learning Model and Its Acceptance among Science Students: Evidence from Introductory Physics Classrooms - Shofiyah, Noly; Jatmiko, Budi; Suprapto, Nadi (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Low levels of student engagement and scientific reasoning skills in science education remain a major concern in higher education. This study aims to explore university students' responses after participating in science learning facilitated by the Data-Based Learning Cycle (DaBeLCy) model. The participants were students from three different universities enrolled in introductory physics courses that implemented the DaBeLCy approach. A survey method was employed using a structured questionnaire designed to assess five key aspects: students' perceptions of the model, conceptual understanding, scientific reasoning skills, learning engagement, and the perceived supportiveness of the learning environment. The results revealed that most students responded positively to the implementation of the DaBeLCy model. They reported improved conceptual understanding, greater engagement during class activities, and enhanced critical thinking skills. Furthermore, both the learning environment and lecturer support were perceived as conducive to the effective application of the model. These findings suggest that the DaBeLCy model is well-received by students and holds strong potential for improving the quality of science education in higher education. Further studies are recommended to examine its effectiveness across diverse learning contexts and disciplines.